(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce some types of separation axioms via F-open sets, namely FT_i (i = 0, 1, 2, 3, 4), F-regular and F-normal spaces, and investigate their properties, relationships and characterizations. We show that every FT_i space is a Ti space for i = 0, 1, 2, 3, 4. However, the converse is true whenever X is finite.